Electrocardiographic Pattern in the Newborn During the First Week of Life - Maemunah Affandi; Bambang Madiyono; Sutarto H.; Asikin Hanafiah (Paediatrica Indonesiana, 1976)
One hundred and sixteen babies were given electrocardiogram examination on the 1st day until the 7th day of birth as well as the examination at 3 and 6 months. There were definite changes in the heart rate, P duration, PR interval, T axis, and T wave of the right precordial leads on the 1st day, especially on the 1st hours of birth. These changes may be caused by physiological adjustment after birth and anatomical changes like the closing of foramen ovale and ductus arteriosus. There were changes on the second day and thereafter caused by increased activities of the left side of the heart. Observations were made on ECG examination on fullterm normal babies on the 1st week of birth. Genetic factors should not be ignored (Sutin and Schrire, 1964) as data gathered in this study have shown some differences from data gathered in other studies.